Towards dynamic contract extension in supplier development - Karl Worthmann; Michael Proch; Philipp Braun; Jörg Schlüchtermann; Jürgen Pannek (Logistics Research, 2016)
We consider supplier development within a supply chain consisting of a single manufacturer and a single supplier. Because investments in supplier development are usually relationship-specific, safeguard mechanisms against the hazards of partner opportunism have to be installed. Here, formal contracts are considered as the primary measure to safeguard investments. However, formal contracts entail certain risks, e.g., a lack of flexibility, particular in an ambiguous environment. We propose a receding horizon control scheme to mitigate possible contractual drawbacks while significantly enhancing the supplier development process and, thus, to increase the overall supply chain profit. Our findings are validated by a numerical case study.
Keywords: 650; Supply chain management; Supplier development; Optimal control; Receding horizon scheme; Dynamic systems